2017
DOI: 10.1038/nmat4857
|View full text |Cite
|
Sign up to set email alerts
|

Strong evidence for d-electron spin transport at room temperature at a LaAlO3/SrTiO3 interface

Abstract: 3A two-dimensional electron gas (2DEG) generated between LaAlO 3 (LAO) and SrTiO 3 (STO) consists of itinerant d-orbital electrons in the t 2g orbitals of Ti in STO 1,2 . This anisotropic orbit induces ferromagnetism, superconductivity, and even their coexistence at LAO/STO interfaces [3][4][5][6][7][8] . The subbands of LAO/STO interfaces have a complicated structure and cross each other due to the strong orbital hybridization 9-12 , resulting in the enhancement of spin-orbit coupling and nonmonotonic gate tu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 45 publications
2
38
0
Order By: Relevance
“…The small spintransfer capability of LSMO across LAO is ultimately motivated by the large LSMO/LAO energy barrier for tunneling (equal to 3.5 eV according to our calculations). This small and confined magnetization is compatible in magnitude with the nul result of XMCD measurements, considering that such tiny effect may be plausibly washed out by extrinsic aspects, such as structural disorder, doping and presence of a LSMO dead-layer, which explains the spread of results found in literature [18][19][20]22]. Overall, our results indicate that spin transfer from LSMO to the 2DEG is actually possible for the pristine heterostructure, although difficult to achieve in practice.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The small spintransfer capability of LSMO across LAO is ultimately motivated by the large LSMO/LAO energy barrier for tunneling (equal to 3.5 eV according to our calculations). This small and confined magnetization is compatible in magnitude with the nul result of XMCD measurements, considering that such tiny effect may be plausibly washed out by extrinsic aspects, such as structural disorder, doping and presence of a LSMO dead-layer, which explains the spread of results found in literature [18][19][20]22]. Overall, our results indicate that spin transfer from LSMO to the 2DEG is actually possible for the pristine heterostructure, although difficult to achieve in practice.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, the presence or the lack of a spin-resolved charge could be then crucially related to the very specific characteristics of the considered sample. According to this interpretation, spin-polarized transport in LAO/STO would be a substantially fragile occurrence, thus accounting for the apparent contrast in the existing literature between cases of substantial [18][19][20] or marginal [22,23] presence of spin-polarization at the LAO/STO interface as transferred from FM electrodes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, the STO/LAO heterostructure can enable potential spintronic innovations and now is attracting rising research interests. [8][9][10][11][12][13] Experimentally, Narayanapillai et al 8 have reported an extremely strong charge current induced Rashba field in the 2DEG layer, which verifies the presence of strong Rashba SOC predicted at the STO/LAO interface. Most recently, the inverse Edelstein effect at the STO/LAO interface has been demonstrated by using the spin pumping technique, [10][11][12] which shows a notable spin-to-charge conversion.…”
mentioning
confidence: 84%
“…Two-dimensional electron system (2DES) realized at the oxide surface or interface is a promising candidate for emergent physical properties and functionalities (1). Since it naturally hosts the spatial inversion symmetry breaking due to the structural asymmetry or crystal symmetry, characteristic spin-split bands with the spin-momentum locking emerge due to spin-orbit interaction (SOI), offering rich spintronic functionalities (2,3). Although 2DES is also an important platform for the exotic quantum phases such as quantum Hall effect (4) and superconductivity (5,6), the effect of the symmetry breaking on such quantum phases has been elusive.…”
Section: Introductionmentioning
confidence: 99%